Strategi Manajemen Kewirausahaan Jasa Pendidikan Berbasis Teknologi Digital: Kajian Literatur dalam Perspektif Revolusi Industri 4.0 - Rachmat Panca Putera; Yuli Supriani; Nova Triana; Asri Fatmala; Muhammad Khoerudin; Naya Fakhita Rizki (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The advancement of the Fourth Industrial Revolution demands strategic transformation in education, particularly in managing educational service entrepreneurship. This article aims to explore how digital-based managerial strategies can be implemented in educational entrepreneurship through a comprehensive literature review approach. The method employed is a systematic literature study based on recent scholarly sources relevant to digital entrepreneurship within educational contexts. The findings reveal that the implementation of digital entrepreneurship management requires organizational readiness, technological adaptation, and innovation in the design of entrepreneurial learning programs. Additionally, collaborative organizational development and theory- and data-driven program evaluation are critical components for ensuring sustainability. The design of new entrepreneurial programs that are adaptive and experiential is also essential to building a competitive educational entrepreneurship ecosystem. These findings imply the urgent need for a strategic repositioning of educational entrepreneurship management to respond to global dynamics and prepare human resources who are innovative and responsive to digital transformation.